Pneumococcal lactational mastitis in a healthy woman. Issue 11 (29th November 2022) - Ujita, Ayaka; Ryu, Hikohaku; Kobayashi, Hiroyuki; Kato, Mikiro
Abstract : We report a case of lactational mastitis complicated by Streptococcus pneumoniae bacteraemia in a breast feeding, healthy woman in her 20s. Numerous investigations showed that mastitis was the probable source of S. pneumoniae bacteraemia. While S. pneumoniae is known to cause non-lactational mastitis in patients with underlying diseases, such as systemic lupus erythematosus, reports of lactating mastitis in healthy individuals are scarce, with only six cases reported in the scientific literature published in English since 1995. Similar to previous reports, our patient had a good clinical course with antimicrobial therapy, and the infection was presumably transmitted from the asymptomatic child to the mother. Although the exact mechanisms that establish transmission from a child remain unclear, both host and pathogen factors, such as stagnant milk or bacterial virulence factors, are thought to play a key role. Caution should be exercised because serotypes not currently covered by pneumococcal vaccines are emerging.